Transcranial direct current stimulation combined with physical or cognitive training in people with Parkinson's disease: A systematic review - Beretta, Victor Spiandor [UNESP]; Conceição, Núbia Ribeiro [UNESP]; Nóbrega-Sousa, Priscila [UNESP]; Orcioli-Silva, Diego [UNESP]; Dantas, Luana Karla Braz Fonseca [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP]; Vitório, Rodrigo [UNESP] (Springer Nature, 2020)
Background: Pharmacologic therapy is the primary treatment used to manage Parkinson's disease (PD) symptoms. However, it becomes less effective with time and some symptoms do not respond to medication. Complementary interventions are therefore required for PD. Recent studies have implemented transcranial direct current stimulation (tDCS) in combination with other modalities of interventions, such as physical and cognitive training. Although the combination of tDCS with physical and cognitive training seems promising, the existing studies present mixed results. Therefore, a systematic review of the literature is necessary. Aims: This systematic review aims to (i) assess the clinical effects of tDCS when applied in combination with physical or cognitive therapies in people with PD and; (ii) analyze how specific details of the intervention protocols may relate to findings. Methods: The search strategy detailed the technique of stimulation, population and combined interventions (i.e. cognitive and/or physical training). Only controlled studies were included. Results: Seventeen of an initial yield of 408 studies satisfied the criteria. Studies involved small sample sizes. tDCS protocols and characteristics of combined interventions varied. The reviewed studies suggest that synergistic effects may be obtained for cognition, upper limb function, gait/mobility and posture when tDCS is combined with cognitive and/or motor interventions in PD. Conclusion: The reported results encourage further research to better understand the therapeutic utility of tDCS and to inform optimal clinical use in PD. Future studies in this field should focus on determining optimal stimulation parameters and intervention characteristics for maximal benefits in people with PD.
Keywords: Cognition; Movement disorders; Neurodegenerative disease; Physical therapy; Rehabilitation; Transcranial stimulation